HIV Impacts CD34+ Progenitors Involved in T-Cell Differentiation During Coculture With Mouse Stromal OP9-DL1 Cells - Tsukamoto, Tetsuo (Frontiers in Immunology, 2019)
HIV-1 causes the loss of CD4+ T cells via depletion or impairment of their production. The latter involves infection of thymocytes, but the involvement of hematopoietic CD34+ cells remains unclear even though HIV-positive patients frequently manifest myelosuppression. In order to have a closer look at the impact of HIV-1 on T-lineage differentiation, this study utilized the OP9-DL1 coculture system, which supports in vitro T-lineage differentiation of human hematopoietic stem/progenitor cells. In the newly developed in vitro OP9-DL1/HIV-1 model, cord-derived CD34+ cells were infected with CXCR4-tropic HIV-1NL4-3 and cocultured. The HIV-infected cocultures exhibited reduced CD4+ T-cell growth at weeks 3–5 post infection compared to autologous uninfected cocultures. Further assays and analyses revealed that CD34+CD7+CXCR4+ cells can be quickly depleted as early as 1 week after infection of the subset, and this was accompanied by the emergence of rare CD34+CD7+CD4+ cells. A subsequent theoretical model analysis suggested potential influence of HIV-1 on the differentiation rate or death rate of lymphoid progenitor cells. These results indicate that CXCR4-tropic HIV-1 strains may impact the dynamics of CD34+CD7+ lymphoid progenitor cell pools, presumably leading to impaired T-cell production potential.